Successful Model of Implementation of the Pentahelix Concept in Developing Cultural-Based Tourism Destinations in Aeng Tong – Tong Village - Rahman, A.Faidlal; Wardana, Azna Abrory (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
Successful Model of Implementation of the Pentahelix Concept in Developing Cultural-Based Tourism Destinations in Aeng Tong – Tong Village. Aeng Tong-Tong Village has become a successful example of implementing the Pentahelix concept for developing a culture-based tourism village. This research explores the role of five main actors—government, academia, business, media, and community—in this development process. The government plays a role in providing policies and infrastructure, while academics contribute through research and training. Local businesses offer facilities and services, the media promotes the village, and local communities directly implement tourism activities. The synergy between these actors has boosted the local economy, preserved culture, and improved infrastructure. These findings show that the Pentahelix collaboration effectively creates sustainable and inclusive tourist destinations. The Aeng Tong-Tong Village Model can be used as a reference for other villages that want to develop their tourism potential with a similar approach.